“Establishing healthy habits and lifestyles early is very important”: parental views of brain health literacy on dementia prevention in preschool and primary school children - Chalhoub, Tayla M.; Mackenzie, Erin; Siette, Joyce (Frontiers in Public Health, 2024)
Introduction Parents have the potential to drive healthy lifestyle behaviors through educational initiatives. This study aims to understand the prevalent thoughts and perceptions parents have toward brain health educational programs for preschool and primary school settings, whilst also contributing to a comprehensive understanding of the role parents can play in the broader context of dementia reduction strategies and the cultivation of brain health awareness among children. Methods Parents with children aged between 2 and 11 years old were interviewed about their current knowledge of dementia, prior beliefs, current lifestyle factors and opinions on educating their children from a young age on the topic of dementia literacy. Thematic deductive analysis was employed to systematically categorize and interpret the qualitative data obtained from these interviews. Results Thirty parents (Mage = 38.6, SD = 4.9, Range = 32–48) identified three core themes on nurturing bodies and minds (e.g., conceptualizing the link between intellectual engagement, continuous learning, and the prevention of cognitive decline), brain health literacy (e.g., current knowledge and awareness of brain health, dementia and associated stigma, and provision of age-appropriate health literacy) and parental concerns (i.e., barriers to initiating conversations about dementia with children and strategies to address and alleviate parental concerns). Parents possessing prior knowledge of dementia and its modifiable risk factors exhibited greater propensity to educate their children on the associated risk factors. Conclusion Our study highlights the vital influence of parents’ experiences, health literacy, and education on the acceptance of brain health education for children. Future interventions should target stigma reduction, enhance awareness, and offer accessible information on modifiable dementia risk factors, enabling a conducive environment for active parental involvement in educating children about brain health and contributing to future well-being.